Integrating Qualitative and Quantitative Methods in Sustainable Finance to Guide Public Policy for Green Investments - Supriadi, Iman; Maghfiroh, Rahma Ulfa; Abadi, Rukhul (JAMPE (Journal of Asset Management and Public Economy), 2025)
This study investigates the role of sustainable finance in advancing investments in renewable energy and green technologies while addressing associated challenges and opportunities. The research aims to analyze the impact of sustainable finance strategies on investment flows, identify key barriers to their effective implementation, and propose strategic recommendations to enhance investment in this sector. This study seeks to support the global transition to a greener and more sustainable economy by optimizing policies, funding mechanisms, and financial practices. Using a mixed-methods approach, this study integrates qualitative and quantitative analyses, including literature reviews, causality analyses, and country-specific case studies. Secondary data generated from industry reports, academic publications, and financial databases form the basis of the analysis. Findings from the Sustainable Finance-Investment Interaction Model reveal that sustainable finance significantly enhances renewable energy investments. However, high initial costs, policy uncertainty, and restricted access to finance remain substantial obstacles. Despite these challenges, opportunities driven by technological advancements and increasing global climate awareness provide a strong foundation for growth. This paper presents recommendations for governments, investors, and financial institutions to strengthen the role of sustainable finance in accelerating renewable energy investments. Emphasizing integrating environmental, social, and governance (ESG) factors into financial decision-making, the study highlights the need for supportive policies to address financing barriers. By aligning financial systems with sustainability objectives, this research contributes to the broader discourse on sustainable finance and underscores its transformative potential in driving the global green transition.